(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Shortage of water for industrial and commercial use and even for drinking purpose is a concern throughout the world, especially in developing countries. The current decline in groundwater availability in India necessitates the formulation of sustainable groundwater management plan through proper assessment of the available resources. Rainwater harvesting (RWH) for groundwater recharge is seen as one of the solutions to solve the groundwater problem. This is reflected in an increase in watershed development programs, in which RWH is an important structural component. Understanding the net effect of these development programs is crucial to ensure that net effect on groundwater is positive both locally and within a watershed. The appropriate design and evaluation of a RWH system is necessary to improve system performance and the stability of the water supply. This review article is focused on a literature survey of the design of RWH and its aquifer modeling and application of remote sensing and geographic information system to artificial recharge.